Revenge Reflected In John Grisham The Racketeer (2012): A Psychoanalytic Approach - Pradita, Gitti Febriani; , Dr. Phil. Dewi Chandraningrum, M. Ed (2016)
This research intends to describe about Malcolm Bannister revenge. The objective of this study is to analyze this novel based on the Individual Psychoanalytic Approach. The writer uses two data sources: primary and secondary. The primary data source of the study is The Racketeer novel by John Grisham. Secondary data are the supporting data taken from literary books, and some articles related to the novel. The secondary data of the study are also taken from any information related to the novel. The method of data collection is the researcher employs the descriptive qualitative research. Based on the analysis, the researcher gets some conclusions. The study shows that the problem by the major character is his revenge. The story tells about revenge of the injustice of Malcolm Bannister who is imprisoned of money laundering case involving him. He is a lawyer. He has his own way to exact his revenge against those who have been defamed as a lawyer.